Sesquiterpene lactone, a potent drug molecule from artemisia pallens wall with anti-inflammatory activity - Ruikar, Anjali D.; Misar, Ashwini V.; Jadhav, Ravindra B.; Rojatkar, Supada R.; Mujumdar, Arvind M.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Arzneimittel-Forschung-Drug Research, 2011)
The present study was carried out to investigate the anti-inflammatory activities of bioactive secondary metabolites of Artemisia pallens Wall, an aromatic herb from family Asteraceae. The results provide evidence for the topical anti-inflammatory properties of Artemisia pallens Wall. The compounds were isolated from the acetone extract of the plant material. The isolates were tested on Swiss albino mice using 12-O-tetradecanoyl phorbol-13-acetate (TPA) induced ear edema. One of the molecules from the extract indicated potent anti-inflammatory activity equivalent to indometacin (CAS 53-86-1). Elucidation of the molecular structures by single crystal x-ray diffraction studies revealed the conformational differences that the six membered rings in both the molecules are at an angle of 28.79 degrees. Presence of hydroxy function for compound 2 may be responsible for higher potency.
Keywords: Anti-inflammatory activity; Artemisia pollens; Asteraceae; Mice; Single crystal x-ray structure